Evolution of plasmids and their role in bacterial diversity and adaptability - Thomas, Christopher (Henry Stewart Talks, 2008)
Why are plasmids important?, Plasmids and gene exchange, Pseudomonas plasmids illustrate diversity through modular structures, Plasmid backbones and their building blocks, IncP-1 plasmids as an example of sophisticated circuitry to extend host range and minimize burden on host